Comparison of Foot Muscle Activity During Short Foot and Toe Spread-out Exercises in Different Weight Bearing Conditions in Individuals With Pes Planus - Hyun-ji Lee; Sae-hwa Kim; Seung-min Baik; Heon-seock Cynn (Korean Research Society of Physical Therapy, 2024)
Background: Individuals with pes planus tend to overuse the extrinsic foot muscles, such as the tibialis anterior (TA) and peroneus longus (PL), to compensate for the weakened intrinsic foot muscles, such as the abductor hallucis (AbdH). Furthermore, differences in weight-bearing can affect the activity of muscles in both the intrinsic and extrinsic foot muscles. To date, no study has compared the effects of the short foot exercise (SFE) and toe spread-out exercise (TSO) on intrinsic and extrinsic foot muscle activity and the corresponding ratios in different weight-bearing positions. Objects: To compare the effects of the SFE and TSO on AbdH, TA, and PL activity and the AbdH/TA and AbdH/PL activity ratios in the sitting and standing positions in individuals with pes planus. Methods: Twenty participants with pes planus were recruited. Surface electromyography was used to assess the amplitudes of AbdH, TA, and PL activity. Participants performed both exercises while adopting both the sitting and standing positions. Results: No significant interaction between exercise and position was found regarding the activity of any muscle or ratio of the activity, except for PL activity. We observed a significant increase in AbdH activity during the TSO compared to the SFE, and no significant difference in TA and PL activity between the two exercises. AbdH, TA, and PL activity were significantly higher in the standing position than in the sitting position. Furthermore, the AbdH/PL activity ratio significantly increased in the sitting position, although there was a significant increase in AbdH activity in the standing position. Conclusion: In individuals with pes planus, we recommend performing the TSO in the sitting position, which may increase the activity of the AbdH while concurrently decreasing the activity of the TA and PL, thus strengthening the AbdH.